P5.027 High Prevalence of Undiagnosed HIV Infection in Patients Who Were Not Offered Screening and Patients Who Declined Screening: Evaluation of a Rapid HIV Screening Programme in a U.S. Urban Emergency Department. (13th July 2013) - Hsieh, Y; Beck, K; Kelen, G; Shahan, J; Kraus, C; Laeyendecker, O; Quinn, T; Rothman, R
Abstract : Background: U.S. emergency departments(EDs) have become a cornerstone of the current CDC screening approach for identifying unrecognised HIV-infected patients. However, in spite of intensive efforts many ED screening programmes frequently fail to identify many infected patients. We aimed to investigate the prevalence of undiagnosed infection in an ED with an established HIV screening programme. Methods: An inner-city ED implemented an opt-in rapid oral-fluid HIV screening programme since 2005; during the summer of 2007, HIV testing facilitators offered 24/7 bedside rapid testing to patients aged 18–64 years. During the same period, an HIV seroprevalence study enrolled adult patients who gave consent for use of their blood samples. Known HIV positivity was determined by either chart review or self-report. Serum samples were tested for HIV by EIA and all positives were confirmed by Western blot followed by RNA viral load testing. Results: There were 3, 884 samples, including 153 from known HIV positives for the seroprevalence study. Among the remaining 3, 731 visits, 1, 286(34%) were offered bedside HIV testing; 2, 445(66%) were not. Among those offered, 693 declined, and 561 were tested (32 accepted but were never tested). Seroprevalence data revealed the following rates of undiagnosed HIV infections: 2.0% in those offered versus 5.3% in those not offered(p < 0.001); 2.5% in those who declined, 0.6% in those tested, and 15.6% in those accepted but not tested(p < 0.001). Mean viral load was significantly higher in those not offered the screening as compared to those offered (difference: 63, 441, 95%: 3, 310–123, 572). Conclusion: There was a disporportinately high prevalence of undiagnosed HIV infection in ED patients who were not offered HIV screening and in those who declined screening, versus those who accepted testing. This indicates that even with an intensive established opt-in counsellor-based rapid HIV screening model, significant missed opportunities remain with regard to identifying undiagnosed HIV-infected individuals in the ED.